Bacteria that decompose lignin into biofuels - Yastremska, Larysa; Korniienko, Iryna; Kuznietsova, Olena; Baranovskyy, Mikhaylo (Problems of Environmental Biotechnology, 2024)
The bacteria that decompose lignin into biofuels are discussed.